Competitiveness, commercial blocks, and regional growth - Carlos Azzoni; Paulo Sa-Porto (European Regional Science Association (ERSA), 2005)
The paper analyses the effects of the Mercosul commercial block on export intensity of different regions in Brazil. A gravitational model is employed to explain the intensity of exports of different Brazilian regions according to destination countries, differentiating those pertaining to Mercosul. Besides GDP, population and distance, typical of the gravitational model, indicators of regional competitiveness came out as important to explain regional export performance. The results indicate that the commercial block does not improve the export performance of regions, which are explained by the economic variables included in the model.
Keywords: 330